VALUE FOR MONEY PAJAK REKLAME DAN PENERANGAN JALAN KOTA DENPASAR DAN KABUPATEN BADUNG - Supriyanti, Ni Wayan; Yadnyana, I Ketut (E-Jurnal Akuntansi, 2015)
The purpose of this research is to know the comparative degree application of the concept of value for money in tax revenues ads and tax of roads between towns denpasar with district badung 2009-2013 years.Engineering analysis used is technique quantitative analysis by uses statistics descriptive.Based on the analysis known that level economical and efficiency city denpasar and regent badung in tax revenues reeklame and tax of roads were very efficient.Level effectiveness city denpasar in tax revenues ads and street lighting and effectiveness district badung in tax revenues street lighting were very effective, but effectiveness acceptance of tax revenues in thousand badung appertain very effective.
Keywords: value for money, billboard tax, tax of roads